1993
DOI: 10.1111/j.1365-2915.1993.tb00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of bluetongue in Central America and the Caribbean: initial entomological findings

Abstract: Forty-four species of Culicoides (Diptera: Ceratopogonidae) were caught in insect light traps during the first 2 years of studies on the epidemiology of bluetongue virus in the Caribbean and Central America. Traps were operated near sentinel ruminants which were bled monthly for serologic evaluation and then virus isolation. More than 570,000 individuals were identified. Culicoides insignis Lutz accounted for 90% of the catch, C. filarifer Hoffman/C. ocumarensis Ortiz 5%, C. furens Poey 3% and C. pusillus Lutz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
(2 reference statements)
0
12
0
Order By: Relevance
“…In Central America and the Caribbean, and even in the Lesser Antilles, BTV is widespread (Greiner et al, 1993;Martinez et al, 2011;MacLachlan et al, 2007). This region seems to be a source of BTV for the rest of the continent with neither ecologic nor geographic barriers described to geographically isolate central America from North or South America (Mertens et al, 2009).…”
Section: Btv In Central America and The Caribbeanmentioning
confidence: 99%
See 2 more Smart Citations
“…In Central America and the Caribbean, and even in the Lesser Antilles, BTV is widespread (Greiner et al, 1993;Martinez et al, 2011;MacLachlan et al, 2007). This region seems to be a source of BTV for the rest of the continent with neither ecologic nor geographic barriers described to geographically isolate central America from North or South America (Mertens et al, 2009).…”
Section: Btv In Central America and The Caribbeanmentioning
confidence: 99%
“…Most of the information available for this region is due to the efforts of the Regional Bluetongue team which started to work in the early 1980s (Greiner et al, 1992(Greiner et al, , 1993Thompson et al, 1992) studying the disease over eleven countries in the region. The Bluetongue Regional team and the Interamerican Bluetongue team (Gibbs et al, 1992;Mo et al, 1994) performed a large surveillance over eleven countries in the region.…”
Section: Btv In Central America and The Caribbeanmentioning
confidence: 99%
See 1 more Smart Citation
“…From these arthropods, 18 species were in the country, C. insignis being the most common species. It was demonstrated in that study that most of these Culicoides are able to transmit BTV (Greiner et al 1993). Another study on sheep confirmed the presence of BTV antibodies in 290 out of 370 sera analyzed in all Costa Rican regions except for the Brunca Region (Villagra-Blanco, Dolz & Montero-Caballero 2008).…”
mentioning
confidence: 79%
“…The fact that this species was only captured in the corral supports its potential role in the transmission cycle of BTV. This species together with C. insignis has been captured in corral areas previously (Greiner et al , ).…”
Section: Species Of Culicoides Biting Midges Captured In Cdc Light Trmentioning
confidence: 95%